2012
DOI: 10.1111/j.1432-2277.2012.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus plus early tacrolimus minimization: a phase III, randomized, open-label, multicentre trial in renal transplantation

Abstract: Summary There is increasing interest in tacrolimus‐minimization regimens. ASSET was an open‐label, randomized, 12‐month study of everolimus plus tacrolimus in de‐novo renal‐transplant recipients. Everolimus trough targets were 3–8 ng/ml throughout the study. Tacrolimus trough targets were 4–7 ng/ml during the first 3 months and 1.5–3 ng/ml (n = 107) or 4–7 ng/ml (n = 117) from Month 4. All patients received basiliximab induction and corticosteroids. The primary objective was to demonstrate superior estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 31 publications
1
70
0
3
Order By: Relevance
“…The 2013 Organ Procurement and Transplantation Network and Scientific Registry of Transplant Recipients annual report demonstrated that tacrolimus (Tac), and not CsA, was by far the most frequently used CNI‐based de novo regimen for all solid organ transplantation 11. Previous studies have shown the combination of EVR and Tac to be safe and well tolerated in renal transplant patients 5, 12, 13. An open‐label exploratory study assessed EVR and Tac combination treatment in maintenance renal patients and found no pharmacokinetic interactions when these treatments were given simultaneously 14.…”
Section: Introductionmentioning
confidence: 99%
“…The 2013 Organ Procurement and Transplantation Network and Scientific Registry of Transplant Recipients annual report demonstrated that tacrolimus (Tac), and not CsA, was by far the most frequently used CNI‐based de novo regimen for all solid organ transplantation 11. Previous studies have shown the combination of EVR and Tac to be safe and well tolerated in renal transplant patients 5, 12, 13. An open‐label exploratory study assessed EVR and Tac combination treatment in maintenance renal patients and found no pharmacokinetic interactions when these treatments were given simultaneously 14.…”
Section: Introductionmentioning
confidence: 99%
“…CNI avoidance with mTOR inhibitor therapy from time of transplant was found to preserve efficacy and improve longterm renal function in early randomized trials (7)(8)(9), but more recent studies that have used lower-exposure sirolimus in an attempt to reduce toxicity have found efficacy to be compromised (10,11) and de novo CNI-free immunosuppression with sirolimus and mycophenolic acid (MPA) may be associated with inferior graft outcomes (10)(11)(12). Several randomized trials have compared the efficacy and safety of mTOR inhibitor therapy with reduced-exposure CNI from the time of kidney transplantation versus a standard CNI regimen with MPA therapy (13)(14)(15)(16). Results have demonstrated that immunosuppressive efficacy is maintained, but although an improvement in graft function has been observed (13) a significant difference may not be sustained (17).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, concentration monitoring has been needed to prevent rejection and toxicity risk. Limited studies have been done so far to assess the transplant outcomes with an mTOR inhibitor-based initial regimen with CNI minimization, with the notable ones being the ASSET study (2012) [22][23][24][25][26][27][28][29] In 2012, Langer and associates in their ASSET study compared de novo introduction of very-lowdose tacrolimus (1.5-3 ng/mL) and everolimus (3-8 ng/mL) with low-dose tacrolimus (1.5-3 ng/mL) and everolimus (3-8 ng/mL). These have been used in a combination with oral steroids following basiliximab induction in renal transplant patients.…”
Section: Mammalian Target Of Rapamycin-based Initial Regimen With Lowmentioning
confidence: 99%
“…The incidence of BPAR episodes were significantly higher in verylow tacrolimus group (18.7% vs 7.7%; P = .01). 22 In 2013, Takahashi and associates studied the early introduction of low-dose cyclosporine and everolimus (baseline level or 0-h blood level of 3-8 ng/mL) with standard-dose cyclosporine and MMF (2 g/d) in combination with oral steroids following basiliximab induction in renal transplant patients. In the low-dose cyclosporine group, levels were gradually reduced from 100 to 200 ng/mL to 25 to 50 ng/mL over 6 months, whereas in the standard dose group, cyclosporine was reduced from baseline level of 200 to 300 ng/mL to 100 to 250 ng/mL in month 2 and further maintained at the same level.…”
Section: Mammalian Target Of Rapamycin-based Initial Regimen With Lowmentioning
confidence: 99%